EBRD ACTIVITIES IN THE FIELD OF SUSTAINABLE ENERGY - E. M. Evdokimova (Vestnik MGIMO-Universiteta)
The article focuses on one of the strategic European Bank for Reconstruction and Development (EBRD) sector priorities – sustainable energy. A vast amount of initiatives aiming at efficient energy use have been launched since the late XX century. Among others a pivotal role play the EBRD programmes comprising investments and technical assistance. Within over 20 years of activity the EBRD has gained great experience carrying out projects in the field of energy efficiency and therefore Sustainable Energy Initiative (SEI) was launched in 2006. Sub-sector breakdown include cleaner energy production, industrial energy efficiency, renewable energy, sustainable energy financing facilities for small and medium-scale projects implemented through local banks etc. SEI Phase 1 and 2 had been carried out by the end of 2011. In 2006-2012 the EBRD invested €11 billion in more than 620 projects. In 2012 Phase 3 was launched for the period 2012-2014, financing target – €4,5 to €6,5 billion. SEI accounts for 20-30% of the total EBRD financing volume. The greatest share as a core country of operations receives Russia: total SEI investments – €2,4 billion, number of projects – over 100, avoided greenhouse gases emissions – 18 million tonnes (CO2 equivalent per year), energy savings – 9 million tonnes of oil equivalent per year. Thus the EBRD encourages sustainable low-carbon economic development of the country. The EBRD will further extend sustainable energy activities, combining investments with technical assistance and policy dialogue.